Intrathoracic Pressure Regulation Improves Cerebral Perfusion and Cerebral Blood Flow in a Porcine Model of Brain Injury. (August 2015) - Metzger, Anja; Rees, Jennifer; Kwon, Young; Matsuura, Timothy; McKnite, Scott; Lurie, Keith G.
Abstract : ABSTRACT: Brain injury is a leading cause of death and disability in children and adults in their most productive years. Use of intrathoracic pressure regulation (IPR) to generate negative intrathoracic pressure during the expiratory phase of positive pressure ventilation improves mean arterial pressure and 24-h survival in porcine models of hemorrhagic shock and cardiac arrest and has been demonstrated to decrease intracranial pressure (ICP) and cerebral perfusion pressure (CPP) in these models. Application of IPR for 240 min in a porcine model of intracranial hypertension (ICH) will increase CPP when compared with controls. Twenty-three female pigs were subjected to focal brain injury by insertion of an epidural Foley catheter inflated with 3 mL of saline. Animals were randomized to treatment for 240 min with IPR set to a negative expiratory phase pressure of −12 cmH2 O or no IPR therapy. Intracranial pressure, mean arterial pressure, CPP, and cerebral blood flow (CBF) were evaluated. Intrathoracic pressure regulation significantly improved mean CPP and CBF. Specifically, mean CPP after 90, 120, 180, and 240 min of IPR use was 43.7 ± 2.8 mmHg, 44.0 ± 2.7 mmHg, 44.5 ± 2.8 mmHg, and 43.1 ± 1.9 mmHg, respectively; a significant increase from ICH study baseline (39.5 ± 1.7 mmHg) compared with control animals in which mean CPP was 36.7 ± 1.4 mmHg (ICH study baseline) and then 35.9 ± 2.1 mmHg, 33.7 ± 2.8 mmHg, 33.9 ± 3.0 mmHg, and 36.0 ± 2.7 mmHg at 90, 120, 180, and 240 min, respectively ( P < 0.05 for all time points). Cerebral blood flow, as measured by an invasive CBF probe, increased in the IPR group (34 ± 4 mL/100 g-min to 49 ± 7 mL/100 g-min at 90 min) but not in controls (27 ± 1 mL/100 g-min to 25 ± 5 mL/100 g-min at 90 min) ( P = 0.01). Arterial pH remained unchanged during the entire period of IPR compared with baseline values and control values. In this anesthetized pig model of ICH, treatment with IPR significantly improved CPP and CBF. This therapy may be of clinical value by noninvasively improving cerebral perfusion in states of compromised cerebral perfusion.